Uma breve discussão sobre os possíveis estados ligados para uma classe de potenciais singulares - Pimentel, Douglas R.M. [UNESP]; De Castro, Antonio S. [UNESP] (My University, 2014)
The one-dimensional Schrodinger equation for a class of potentials V (|x|) which vanish at infinity and present dominant singularity at the origin in the form α/|x|β (0 < β ≤ 2) is investigated. The hermiticity of the operators related to observable physical quantities is used to determinate the proper boundary conditions. Double degeneracy and exclusion of symmetric solutions, depending on the value of β, are discussed. Explicit solutions for the hydrogen atom and the Kratzer potential are presented. © by the Sociedade Brasileira de Física.
A brief discussion on the possible bound states for a class of singular potentials
Keywords: Collapse to the center; Degeneracy; Kratzer potential; One-dimensional hydrogen atom; Singular potential